2019
DOI: 10.1097/inf.0000000000002106
|View full text |Cite
|
Sign up to set email alerts
|

Potential for More Rational Use of Antibiotics in Hospitalized Children in a Country With Low Resistance

Abstract: This study reveals an excess of prescriptions with BSA in relation to the low resistance rate in Norway. Our findings reveal areas for improvement that can be useful in the forthcoming antibiotic stewardship programs in Norwegian pediatric departments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 24 publications
1
19
1
2
Order By: Relevance
“…There are no established similar principles for antibiotic consumption analysis in Latvian hospitals, and almost all consumption studies are voluntary and based on researcher enthusiasm. Nevertheless, this is also a problem in many other countries [ 31 , 32 ]. At the moment hospitals in Latvia can choose to conduct or not to conduct antibiotic consumption studies, as well as what methodologies to use.…”
Section: Discussionmentioning
confidence: 99%
“…There are no established similar principles for antibiotic consumption analysis in Latvian hospitals, and almost all consumption studies are voluntary and based on researcher enthusiasm. Nevertheless, this is also a problem in many other countries [ 31 , 32 ]. At the moment hospitals in Latvia can choose to conduct or not to conduct antibiotic consumption studies, as well as what methodologies to use.…”
Section: Discussionmentioning
confidence: 99%
“…A registry-based population study from Norway (2009–2011) showed that half of term-infants receiving antibiotics were not proven to have a bacterial infection (11). Use of BSA in Norwegian neonates is lower than in older children, but empirical choices of antibiotics vary, and there is a lack of evidence on neonatal dose regimes (15, 16).…”
Section: Introductionmentioning
confidence: 99%
“…This proportion is slightly lower than the results of a one-day PPS performed by another group on antibiotic treatment of hospitalized children across nine provinces in China (67.76%) [ 16 ] but much higher than the rate of antibiotic prescription in a tertiary children’s hospital surveyed in Sichuan, China (46.1%) [ 17 ]. Compared with Western countries (Sweden 35.5% [ 18 ], Norway 24% [ 19 ], UK 40.9% [ 20 ], Italy 38.9% [ 21 ]), our study revealed a much higher rate of antibiotic use in China indicating that the use of antibiotics in the treatment of hospitalized children varies by countries and regions. Thus, there is a need to collect and analyze data regarding the use of antibiotics in local regions and even individual hospitals in order to tailor pediatric antibiotic management more effectively.…”
Section: Discussionmentioning
confidence: 66%